Supply Chain Management Agro-Industry Cassava In Indonesia - Dona Wahyuning Laily; Noor Rizkiyah; Ida Syamsu Roidah; Fatchur Rozci; Herry Nur Faisal (Future Science, 2023)
Background: The Cassava supply chain starts from raw materials supplied by farmers and then supplied to factories. Given the vast potential of cassava, especially in the processing industry. Aim: Increasing efficiency in the cassava supply chain, industry players actively participate in increasing productivity and reducing problems from upstream to downstream. Setting: Indonesia. Method: Through field survey activities, focus group discussions (FGD), and reviewing various papers and research studies previously published in various journals, books, magazines, and others. Results: The cassava supply chain originates from farmers with several layers of intermediaries. All farmers' supply chains are traded in cassava flour, tapioca flour, or wet cassava, which is the buyer's responsibility starting from pulling, peeling, drying, and packing. Stakeholders generally support the cassava supply chain by ensuring material, information, and cash flow among all stakeholders to maximize profits and involve cassava growers, cassava mills, and distributors. Conclusion: The development of cassava processed food agro-industry is carried out on a home industry scale because it applies simple technology and is carried out by farmer groups and individuals. The cassava supply chain's development will increase added value and increase the income of farmers and the community.